Penerapan Edukasi Gizi Buruk Pada Generasi Alfa Sebagai Penerus Generasi Milenial di Tanjung Priok Jakarta - Liza Agustina Maureen Nelloh; Mahonri Lukas; Prima Dyah Indira; Rio Kurniawan; Rismatio Rismatio (Journal of Sustainable Community Development (JSCD), 2020)
Millennial generation contributes significantly to the Indonesian economy. This generation has successors who are called the Alfa generations who will inherit and succeed in reaching the Millennial generation. However, based on official Indonesian government data, it is proven that there are still many Alfa Generation children who are malnourished and have special stunting in Tanjung Priok, North Jakarta. This is allegedly due to lack of education of the millennial generation itself regarding malnutrition for children's development. Therefore, this Community Service activity is carried out to provide education for the older generation of Alfa which is mostly obtained from millennial generation. This social activity is carried out in the Church of St. Fransiskus Xaferius, Tanjung Priok, North Jakarta. This activity is conducted to educate their parents to be more concern about healthy lifestyles to update nutrition issues in Indonesia. This activity is useful to increase knowledge and awareness about the importance of a good lifestyle for ASAK (Ayo Sekolah Ayo Kuliah).